Pharmacological mechanisms of Fuzheng Huayu formula for Aristolochic acid I–induced kidney fibrosis through network pharmacology - Wang, Fan; Wang, Siyuan; Wang, Jing; Huang, Kai; Chen, Gaofeng; Peng, Yuan; Liu, Chenghai; Tao, Yanyan (Frontiers in Pharmacology, 2022)
Renal fibrosis, characterized by the destruction of renal tubules and interstitial capillaries and the accumulation of extracellular matrix proteins, is a common outcome of chronic renal diseases and has a wide spectrum of etiologies. Fibrosis can affect any organ and has similar pathological mechanisms. Fuzheng Huayu formula (FZHY), as the approved anti-liver fibrosis medicine in China, also can inhibit the kidney fibrosis induced by HgCl2 or unilateral ureteral obstruction. However, little is known about the mechanisms underlying the beneficial effects of FZHY on renal fibrosis. This study aimed to identify the mechanisms of FZHY acts on renal fibrosis through network pharmacological analysis and in vivo experiments. Data from online databases were mined and screened to predict the target related genes of FZHY acts on renal fibrosis. The STRING and Cytoscape were used to construct the protein-protein interaction (PPI) networks for FZHY and CKD target proteins. Mouse models with CKD induced by Aristolochic Acid I (AAI) were used to validate the effects of FZHY on renal fibrosis and their underlying mechanisms by detecting kidney function, renal fibrosis, and related intersection genes. A total of 129 FZHY–CKD crossover proteins were filtered and constructed into a protein–protein interaction network complex and designated as the potential targets of FZHY. One of the highest-scoring genes, FOS, and its related signaling pathways were more activated in CKD. The results demonstrated that FZHY can exert an anti-renal fibrosis effect by improving the levels of serum creatinine and blood urea nitrogen and alleviating excessive collagen deposition in kidney tissue, FZHY also could reduce the levels of TNF-α, IL-1β, and IL-6 and inhibit the expression of MAPK/FOS signal molecules. Our study findings provide insights into predicting the effects of FZHY on CKD through network pharmacology. FZHY can protect the kidney from inflammatory injury caused by AAI and can antagonize inflammatory factor-stimulated MAPK/FOS activation in fibrotic kidneys. These effects constitute the mechanisms of FZHY for renal fibrosis.